2013
DOI: 10.1063/1.4823520
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the sample preparation in experiments using piezoelectric actuators inducing uniaxial or biaxial strains

Abstract: We report on a systematic study of the stress transferred from an electromechanical piezo-stack into GaAs wafers under a wide variety of experimental conditions. We show that the strains in the semiconductor lattice, which were monitored in situ by means of X-ray diffraction, are strongly dependent on both the wafer thickness and on the selection of the glue which is used to bond the wafer to the piezoelectric actuator. We have identified an optimal set of parameters that reproducibly transfers the largest dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Strain can be dissipated both in the epoxy layer and in the sample itself. The ability of the stack to transmit the strain to the sample therefore depends on the choice of glue and the thickness and elastic properties of the sample [53]. Previously it was found that the strain is essentially fully transmitted for large (i.e.…”
Section: Practical Considerations: Strain Transmissionmentioning
confidence: 99%
“…Strain can be dissipated both in the epoxy layer and in the sample itself. The ability of the stack to transmit the strain to the sample therefore depends on the choice of glue and the thickness and elastic properties of the sample [53]. Previously it was found that the strain is essentially fully transmitted for large (i.e.…”
Section: Practical Considerations: Strain Transmissionmentioning
confidence: 99%
“…Another source of strain comes from mounting the sample to the piezo stack, which creates a "built-in" strain from the epoxy [35]. To test for the effects of built-in strain, the resistivity as a function of temperature was measured with the sample free-standing and when glued to the piezo stack (Figure 5).…”
Section: Proximity To Strain-induced Transitionmentioning
confidence: 99%
“…For tetragonal symmetry, the elastoresistivity tensor m ij has six independent coefficients, which can be determined through a combination of elastoresistance measurements using different sample orientations [27]. We use commercially available PZT piezoelectric stacks (PSt150/5x5/7 cryo 1 from Piezomechanik) to generate anisotropic biaxial in-plane strain, following the general method described in Ref.s [27], [28], and [36]. Crystals are glued to the surface of the piezoelectric stack using five minute epoxy (from ITW Devcon), and electrical contact is made using silver paste onto evaporated gold contacts for standard four-point resistance measurements.…”
mentioning
confidence: 99%